الحوافز الضريبية في القانون الليبي وأثرها في جذب استثمار الشركات الأجنبية (دراسة على ضؤ الشريعة الإسلامية) - Umiema - H - Emhemed Abdu Jawad
There are several phenomena's that attract foreign companies to divert its destination of investment from one country to another that is less flourishing economically. What attracts these companies is the tax incentives offered by these countries. These tax incentives in the general context or investment laws on a more specified level pose an attractive option to foreign companies. The problem in the search is the relationship between tax incentives and foreign companies and their interaction with each other. Therefore a link will be established in this study between the Libyan laws relating to taxation and investments and what incentives do these laws provide to forging companies fi-om one perspective. On the other hand the second perspective to link is the Islamic sharia law taxes which are composed of some money sources, in addition to looking more closely to the extent of impact of the offered tax incentives in relation to the set goals. The study based on both inductive and analytical method isindispensable comparative approachwhenneed to arises. The most important results;These are that foreign companies from the sharia law perspective are more protective of the government than from the Positivism laws. This resulted that these foreign companies should be managed by a Muslim. That action is based on the fact that a business manager should have previous knowledge of the governing sharia laws that the contracts should obey and to reject any contracts that don't satisfy the laws. Sharia laws have always taken the lead of Positivism laws in providing counter measures to insure that taxes are collected. That's through insuring that foreign investment obey the sharia law and forbid these companies from breaking the laws. On the other hand we find what concerns Libyan laws is the tax incentive which is an early indicator to early action of investment in any country. According to the World Investment Report issued in 201 1 that examined the direct investment index of foreign companies in Arab countries, pointed out that Libya has seen a rise of investment flows of more than 40% in 2010 which reach $ 3.8 billion, in comparison to 2005 direct investments of foreign companies was the proportion of foreign flows investment of $ 1 billion. Thus, it is clear that the rise in the flow of foreign investment company's index was the product of Law No. 5. The proof of the success was the number of attracted foreign companies that invested in Libya in 2010. This flow attraction was short-term due to the political crisis that Libya was going through since the beginning of 2012, which resulted in a decline of investments by foreign companies.